The Constitution for Europe - Piris, Jean-Claude (Cambridge University Press, 2013)
In the time-scale of history, sixty years is very short. For centuries, ever since the Greeks and the Romans, since the Normans and the Germans, not to mention the British and the French, the peoples of Europe have constantly waged war on each other. During the last century alone, from 1914 until 1918 and from 1939 until 1945, merciless wars inflamed the European continent causing hatred and massive destruction, leaving its peoples bled white and prey to starvation.